Cerebrovascular Effects of Dotarizine, a Piperazine Derivative, in the Goat - Torregrosa, Germaán; Barberaá, María D; Ortí, Marta; Centeno, José M; Salom, Juan B; Alborcha, Enrique (Arzneimittelforschung, 1999)
The effects of dotarizine (1-(diphenylmethyl)-4-[3-(2-phenyl-1,3-dioxolan-2-yl)propyl]-piperazine, CAS 84625-59-2) on the cerebral circulation of goats were assessed in vivo by recording continuously global cerebral blood flow (gCBF) and cortical perfusion (CP), and in vitro by recording isometric tension in goat isolated middle cerebral artery (MCA). Administration of dotarizine (1 µg-5 mg) directly into the cerebroarterial supply of goats produced transient increases in gCBF and CP, and decreases in cerebral vascular resistance (CVR) which were significant for the highest doses tested: 1, 3 and 5 mg. On the other hand, cumulative addition of increasing concentrations of dotarizine (10-8−3 × 10-5 mol/l) to MCA segments subjected to the resting tone of 1 g did not induce sizeable changes in vascular tension; by contrast, dotarizine elicited concentration-dependent relaxations of MCA segments subjected to the active tone induced by either 5-hydroxytryptamine (10-6 mol/l) or high-K+ medium (50 mmol/ l). These results show that dotarizine exerts a direct relaxant action on cerebral arteries, which results in an improvement of cerebral perfusion.
Keywords: CAS 84625-59-2; Dotarizine, cerebrovascular effects, goat, in vitro and in vivo studies; Piperazine derivative